2020
DOI: 10.26555/ijain.v6i2.466
|View full text |Cite
|
Sign up to set email alerts
|

Lettuce life stage classification from texture attributes using machine learning estimators and feature selection processes

Abstract: Classification of lettuce life or growth stages is an effective tool for measuring the performance of an aquaponics system. It determines the balance in water nutrients, adequate temperature and lighting, other environmental factors, and the system’s productivity to sustain cultivars. This paper proposes a classification of lettuce life stages planted in an aquaponics system. The classification was done using the texture features of the leaves derived from machine vision algorithms. The attributes underwent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The computational root phenotype model consists of processes of root segmentation and root numerical traits extraction. Graph-cut segmentation is a computer vision technique based on energy minimization that computationally determines the arrangement of atoms in physical space or picture elements for images in terms of color features through K-means clustering (Concepcion, Lauguico, Alejandrino, Dadios, & Sybingco, 2020;Lauguico, Concepcion, Alejandrino, Tobias, & Dadios, 2020). It uses lazy snapping that snaps true object pixels from low contrast edges (Concepcion, Lauguico, Alejandrino, Dadios, & Sybingco, 2020).…”
Section: Development Of Computational Root Phenotype Modelmentioning
confidence: 99%
“…The computational root phenotype model consists of processes of root segmentation and root numerical traits extraction. Graph-cut segmentation is a computer vision technique based on energy minimization that computationally determines the arrangement of atoms in physical space or picture elements for images in terms of color features through K-means clustering (Concepcion, Lauguico, Alejandrino, Dadios, & Sybingco, 2020;Lauguico, Concepcion, Alejandrino, Tobias, & Dadios, 2020). It uses lazy snapping that snaps true object pixels from low contrast edges (Concepcion, Lauguico, Alejandrino, Dadios, & Sybingco, 2020).…”
Section: Development Of Computational Root Phenotype Modelmentioning
confidence: 99%
“…These were Logistic Regression, Multilayer Perceptron, and Naive Bayes. Numerous research has shown that these algorithms are able to create accurate models, some even outperform other highly sophisticated classification methods [25,26,27,29]. As such, these three algorithms were chosen for their simple structure, functionality, as well as their availability in the scikit learn software.…”
Section: Machine Learning Algorithmsmentioning
confidence: 99%
“…As of writing, sklearn can only implement univariate filter selection methods and the recursive feature elimination algorithm. As such, Univariate Selection (US) and Recursive Feature Elimination (RFE) were done as implemented by [29].…”
Section: Feature Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each row of combined 18 predictors, the Hampel algorithm computes the median and standard deviation of the 10 samples from each side, and if the original sample is more than thrice the computed standard deviation, it will be replaced by the computed median. Feature-based machine learning is a subset of computational intelligence that trains a predictive model, whether it is for classification or regression, using multiple categorized numerical data as its features (Lauguico, Concepcion II, Alejandrino, Tobias, & Dadios, 2020;Loresco & Dadios, 2018). The features tested in the study were generalized processing regression (GPR), regression-based support vector machine (RSVM), regression tree (RTree), adaptive neuro-fuzzy inference system (ANFIS), and multigene symbolic regression genetic programming (MSRGP).…”
Section: Leaf Photosynthetic Signature Extraction and Selectionmentioning
confidence: 99%